The Role of the Media in Building Democracy in Nigeria: Focus On Freedom of the Press - Shittu Lukman Olayinka; Salahuddin (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
This study investigated the role of media in building democracy in Nigeria: Focus on freedom of the press. The study was guided by three objectives and also answered three research questions. In conducting this study, the researcher used a descriptive survey research design. The study population consist of citizens of Nigeria across the North Central region. From the population a sample size of 200 respondents were selected using multi stage sampling. Multi stage sampling is suitable because it gives room and possibility for all elements to be fairly represented. The instrument used for data collection was a structured questionnaire developed by the researcher. Data was collected using a structured questionnaire developed by the researcher. The instrument was subjected to expert scrutiny to establish content validity. The reliability was also established using internal consistency through Alpha Cronbach method and the reliability coefficient was ascertain at 0.79 which shows that the instrument was reliable. The analysis was performed using descriptive statistics through mean and standard deviation computed using SPSS version 25.0. The analysis revealed among other things that, media is a watchdog of the society and also underscores the role of media in promoting the information and educating the citizenry for healthy democracy. Also that, the freedom of the media should be promoted to promote healthy democracy. The study recommended among other things that, government and stakeholders should ensure strengthening legal protections for journalists to safeguard press freedom and reduce censorship and also should promote media independence by establishing regulatory frameworks that limit government influence and ownership bias among others.